Association of amino acids related to urea cycle with risk of diabetic nephropathy in two independent cross-sectional studies of Chinese adults - Cao, Penglong; Huang, Bing; Hong, Mo; Jiang, Yuxin; Cao, Ran; Chi, Chen; Cao, Yunfeng; Li, Shijun (Frontiers in Endocrinology, 2022)
Objective: To investigate the association between amino acids related to urea cycle and diabetic nephropathy (DN) in two independent cross-sectional studies. Methods: We got the medical records of 145 individuals with DN and 596 individuals without DN who attended annual health examination from Liaoning Medical University First Affiliated Hospital from May 2015 to August 2016. From April 2018 to April 2019, we collected another medical records of 741 individuals including 338 individuals with DN and 403 individuals without DN in the Second Affiliated Hospital of Dalian Medical University, China. Binary logistic regression was used to obtain the odds ratio (OR) and 95% confidence interval (CI). Results: In two independent cross-sectional studies, we observed citrulline were associated with DN risk, consistently (the OR (95% CI) of per SD increase for citrulline in the LMUFAH: 1.200 (1.006,1.432); the OR (95% CI) of per SD increase for citrulline in the DALIAN: 1.189(1.012,1.396); the pooled effect size for citrulline: 1.194(1.060,1.345)). However, ornithine, arginine and the ratio of arginine to ornithine were consistently unrelated to DN risk while the ratio of other amino acids in the urea cycle are inconsistently associated with DN risk in two independent cross-sectional studies. Conclusions: Citrulline was consistently associated with DN risk in two independent cross-sectional studies in Chinese adults. Keywords: diabetic nephropathy, urea cycle, amino acids, association